Indentation creep study on metal composite solder with different particle size - Liu, Ye. (2013)
To enhance the creep resistance of eutectic Sn-58Bi solder alloy, low concentration of copper fillers with two sizes, i.e. 3μm and 45μm, have been added into alloys respectively. Their elastic modulus, hardness and creep stress exponent were characterized by using nanoindentation constant strain rate (CSR) technique. Scanning electron microscope (SEM) was also used to observe microstructure of all the samples before and after indentation. The results show that small amount (less than 2wt %) of copper fillers of both sizes lead to microstructure refinement and thus an increase in modulus and hardness. However, larger amount (more than 2wt %) of filler addition result in agglomeration of intermetallics compounds, and hence compromise the mechanical properties. This phenomenon is especially serious for copper particles with larger size (45μm). By studying the strain rate-stress relationship, two regions of creep stress exponents were found in all the sample alloys. Combining the observation of deformation using SEM, the dominant creep mechanism is dislocation climb at high stress region, and phase boundary sliding at low stress region. The transition stress region is around 170MPa to 200MPa. When copper concentration is the optimum at around 2wt% for both sizes of copper particles, the maximum enhancement of creep resistance is achieved under counter-actions of pinning effect and microstructure refinement. At last, the effect of annealing is also explored, and it proves the alloys’ modulus, hardness and creep resistance can be effectively improved by annealing, because most of aggregates have been dissolved.